AUDIT QUALITY MODERATES CORPORATE SOCIAL RESPONSIBILITY AND GOOD CORPORATE GOVERNANCE RELATIONS ON FIRM VALUE - Dian Pratiti; Holiawati; Suripto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to examine the moderating effect of Audit Quality on the relationship between Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on Firm Value. The research is classified as quantitative associative research. Secondary data, obtained from www.idx.co.id and the respective company websites, were used in this study. The population comprises companies in the energy sector listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. The sample was determined using purposive sampling, resulting in 30 companies being selected. The analysis method employed is Panel Data Regression Analysis. The findings of this study indicate that CSR does not affect Firm Value, while GCG has a positive impact on Firm Value. Audit Quality can moderate and weaken the positive relationship between Corporate Social Responsibility and Firm Value and Audit Quality cannot moderate the relationship between Good Corporate Governance and Firm Value.